Politeia and koinōnia studies in ancient Greek history in honour of Josine Blok - Pirenne-Delforge, Vinciane 1963-; Węcowski, Marek 1969-; Blok, Josine 1953- (Brill, 2023)
"Politeia and Koinonia are forms of government and citizenship, community and participation, from Sappho's social and political status to the economic and religious activity of women, from the reforms of Solon to the French Revolution. This book by leading scholars in ancient Greek history explores the most important aspects of Greek civilization and those that stirred the most our modern curiosity and our modern perceptions of Greek antiquity. The reason to organize this unique international exchange of ideas was to celebrate the outstanding scholarly achievement of Professor Josine Blok on the occasion of her retirement in 2019"--
Keywords: Geschichte; Griechenland -- Altertum; Greece / Civilization / Historiography; Civilization, Classical / Historiography; Greece / Historiography; Civilization / Greek influences; Civilization / Historiography; Historiography; Greece; Aufsatzsammlung